The Concept of the Massive Photon and its Astrophysical Implications - Saiyan, G. A.
We discuss the concept of the massive photon with its possible implications in astrophysics. We use the term ”mass equivalent” instead of relativistic or effective mass. We also analyzed modified Planck’s law and estimated (mean mass/rest mass) ratio in connection to the temperature of blackbody radiation of the massive photons. This ratio diverges at high temperatures and approaches unity at low temperatures.The ”mass equivalent” for the CMB radiation was estimated to be equal to 0.0468% of the total mass of the Universe. We have discussed importance of the Breit-Wheeler process of particle – antiparticle production in the early Universe. We have evaluated the upper limit of the rest mass of the photon using gravitational and cosmological redshifts. A correlation was found between estimated masses of the photon and the lowest/highest frequencies of the spectral bands used for estimation of the mass.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture